Spectrum of Ophthalmic Diseases in Children at a Referral Hospital - Asad Aslam Khan, Zahra Khalif Bile, Shakeel Ahmad (Pakistan Journal of Ophthalmology, 2007)
Purpose: To give an overview of diseases seen at a tertiary care hospital pediatric ophthalmology outpatient clinic in Punjab. Material and Methods: A descriptive retrospective study was done of patients visiting the paediatric ophthalmology clinic from May 2004 to April 2005 by accessing the OPD registers kept by the hospital. Patients were categorized into ten different groups, using an anatomical classification. The age categories were divided into three groups, children below the age of one, ages1-5 years and the older children were placed in the six to fifteen years category. Results: A total number of 3289 children were included with a male 63.6% and females 36.4% and the mean age was 5.1 years. Diseases of lens effected 33% of the patients examined. Squint was the second most common disorder seen affecting 17% of these children. Errors of refraction affected 15% and oculoplastic 9%. Trauma was an important cause of morbidity in 10% of these children and corneoscleral tear was the main culprit. The rest of the conditions were glaucoma 6%, conjunctival diseases 4%, vitreoretinal 3%, orbital 3% and miscellaneous 3%. Conclusion: In this study, boys were found to be more often affected with eye diseases and the presentation to a tertiary care hospital was most often late. Most paediatric eye diseases need special care and early intervention; therefore it is crucial that good provincial and district paediatric ophthalmology centers are set up. More than 1500 children per year may need surgery in a busy tertiary care hospital, therefore expansion of facilities and training more health professions is important.